'True, Publick and Notorious': The Privateering War of 1812. (20th August 2021) - Kert, Faye M.
Abstract : page_53 other During the War of 1812, hundreds of private armed vessels, or privateers, carrying letters of marque and reprisal from their respective governments, served as counterweights to the navies of Great Britain and the United States. By 1812, privateering was acknowledged as an ideal way to annoy the enemy at little or no cost to the government. Local citizens provided the ships, crews and prizes while the court and customs systems took in the appropriate fees. The entire process was legal, licensed and often extremely lucrative. Unlike the navy, privateers were essentially volunteer commerce raiders, determined to weaken the enemy economically rather than militarily. So successful were they, that from July 1812 to February 1815, privateers from the United States, Britain, and the British provinces of New Brunswick and Nova Scotia (as well as those sailing under French and Spanish flags) turned the shipping lanes from Newfoundland to the West Indies, Norway to West Africa, and even the South Pacific into their hunting grounds. In the early months of the war, privateers were often the only seaborne force patrolling their own coasts. With the Royal Navy pre-occupied with defending Britain and its Caribbean colonies from French incursions, there were relatively few warships available to protect British North American shipping from their new American foes. Meanwhile, the United States Navy had only a handful of frigates and smaller warships to protect their trade, supported by 174 generally despised gunboats. The solution was the traditional response of a lesser maritime power lacking a strong navy—private armed warfare, or privateering.